Intimate revelations: conversations among “evil” women in Rokeya’s Padmarag - Hasan, Md. Mahmudul (SAGE Publications, 2019)
Rokeya creatively demonstrates in Padmarag (1924) the socially embedded association of women with evil. She brings together a group of women on the premises of Tarini Bhaban in order to explore their psychological terrain, as they share with each other previously untold memories and document their experiences of patriarchal oppression and domestic abuse. Through their reminiscences and memories, Rokeya lays bare the angst of women in a patriarchal social order that silences and suppresses them. Beyond the premise of sisterhood at Tarini Bhaban, in one way or another, most of these women are considered “evil” in society as a whole. For example, Saudamini is a stepmother with no biological children of her own and is regarded as a dakini (witch) and rakshasi (a female demon). Other women of Tarini Bhaban have received comparable tags from society and experienced similar victimization. Based on the representation of “evil” women in the novel, in this article I will discuss their stories and examine some of the contributing factors to their victimization and characterization as wicked in the context of early twentieth-century Bengal.